1978
DOI: 10.1097/00000658-197802000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Late Failure in Vein Grafts

Abstract: Late failure of autologous vein grafts often results from excessive subendothelial fibromuscular hyperplasia. Varying factors have been implicated in this process, but the exact etiology remains unclear. In this study, three groups of animals were studied which had sections of common carotid artery replaced with autologous vein grafts. Group I had simple replacement, while Groups II and III had grafts supported by either tightly woven or loose mesh dacron prostheses. Thrombosis occurred only in the unsupported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(11 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…These include mechanical stretch, 6 conduit distension using a hand-held syringe for identification of leaks and side branches, 7 marking of the conduit using surgical skin markers for purposes of orientation, 8 and vein conduit storage in acidic solutions. 9 The surgical literature has focused primarily on the histologic and morphologic changes occurring to the vein graft following surgical harvest and preparation, including disruption of the vasa vasorum, 10 surgical trauma to the endothelium, 11 and tunica media. 12 However, the degree to which these morphologic changes impact the cellular viability and physiology of the HSV graft has not been well investigated.…”
mentioning
confidence: 99%
“…These include mechanical stretch, 6 conduit distension using a hand-held syringe for identification of leaks and side branches, 7 marking of the conduit using surgical skin markers for purposes of orientation, 8 and vein conduit storage in acidic solutions. 9 The surgical literature has focused primarily on the histologic and morphologic changes occurring to the vein graft following surgical harvest and preparation, including disruption of the vasa vasorum, 10 surgical trauma to the endothelium, 11 and tunica media. 12 However, the degree to which these morphologic changes impact the cellular viability and physiology of the HSV graft has not been well investigated.…”
mentioning
confidence: 99%
“…A limitation of these studies is that only the final vascular changes associated with grafting can be determined. To elucidate the sequence of changes, vascular grafts have been performed in experimental animals (Brody et al, 1972a(Brody et al, , 1972bFonkalsrud et al, 1978;Karayannacos et al, 1978) using venous tissue from different locations. It was concluded from these studies that the necrosis may result from hypoxia associated with disruption of the vasa vasorum, while the increase in wall thickness may be due to the elevated transmural pressure associated with placing the vein in the arterial circulation.…”
mentioning
confidence: 99%
“…However, it has been shown that complement and mast cells migrate onto NH‐reducing macroporous polyester sheaths and deposit ECM proteins. Lymphocytes, neutrophils, giant cells, and T‐cells were shown to be entrapped by these sheaths, but not with the ineffective microporous ePTFE stents . In general, substrates with higher surface area‐to‐volume ratios such as porous materials exhibit higher ratios of macrophages and foreign body giant cells, whereas smooth surfaces with low surface area‐to‐volume ratios exhibit a significant degree of fibrosis.…”
Section: Design Considerations For External Stentingmentioning
confidence: 99%
“…The authors speculated that by preventing over‐distention, the diameter of the vein could better match that of the artery and reduce turbulence that leads to thrombosis. Using the same canine model in 1978, Karayannacos et al became the first to observe that an external mesh around a vein could reduce NH by preventing dilation of the vein graft . Given that the loose‐fitting Dacron (poly(ethylene terephthalate)) meshes promoted a higher degree of neovasa vasorum and less intimal‐medial thickness than a tightly woven Dacron sheath, the authors deduced that Dacron meshes reduced NH by promoting formation of neovasa vasorum that minimize ischemic conditions inducing VSMC proliferation.…”
Section: External Stentsmentioning
confidence: 99%